Effects of Surface Topography and Vibrations on Wetting: Superhydrophobicity, Icephobicity and Corrosion Resistance - (:unkn) unknown (My University, 2016)
Concrete and metallic materials are widely used in construction and water industry. The interaction of both these materials with water and ice (or snow) produces undesirable results and is therefore of interest. Water that gets absorbed into the pores of dry concrete expands on freezing and can lead to crack formation. Also, the ice accretion on concrete surfaces such as roadways can have disastrous consequence. Metallic components used in the water industry undergo corrosion due to contact with aqueous corrosive solutions. Therefore, it is desirable to make concrete water/ice-repellent, and to make metallic surfaces corrosion-resistant. Recent advances in micro/nanotechnology have made it possible to design functional micro/nanostructured surfaces with micro/nanotopography providing low adhesion. Some examples of such surfaces are superhydrophobic surfaces, which are extremely water repellent, and icephobic surfaces, which have low ice adhesion, repel incoming water droplets before freezing, or delay ice nucleation. This dissertation investigates the effects of surface micro/nanotopography and small amplitude fast vibrations on the wetting and adhesion of concrete with the goal of producing hydrophobic and icephobic concrete, and on the wetting of metallic surfaces to prevent corrosion. The relationship between surface micro/nanotopography and small fast vibrations is established using the method of separation of motions. Both these small scale effects can be substituted by an effective force or energy. The structure-property relationships in materials and surfaces are established. Both vibrations as well as surface micro/nanopatterns can affect wetting properties such as contact angle and surface free energy. Hydrophobic engineered cementitious composite samples are produced by controlling their surface topography and surface free energy. The surface topography is controlled by varying the concrete mixture composition. The surface free energy of concrete is lowered using a hydrophobic emulsion. The hydrophobic concrete samples were able to repel incoming water droplets as well as resist droplet pinning. Corrosion resistance is achieved in cast iron samples by rendering them superhydrophobic. The corrosion resistance of superhydrophobic surfaces with micro/nanotopography may be explained by the low effective contact area with the electrolyte. The experimental results matched the theoretical predictions based on surface roughness and wettability. The icephobicity of engineered cementitious composite samples is achieved by hydrophobization, by using coatings containing dielectric material (such as polyvinyl alcohol fibers), and by controlling the surface topography. Two aspects of the icephobicity of concrete, namely, the repulsion of incoming water droplets before freezing and the ice adhesion strength, are investigated experimentally. It is found that icephobic performance of concrete depends on these parameters – the hydrophobic emulsion concentration, the polyvinyl alcohol fiber content, the water to cement ratio, and the sand to cement ratio. The potential for biomimetic icephobicity of thermogenic skunk cabbage plant is investigated, and it is found that the surface topography of its leaves can affect the heat transfer from the plant to the surrounding snow. The hierarchical microstructure of the leaf surface coupled with its high adhesion to water suggests the presence of an impregnated wetting state, which can minimize the heat loss. Thus functional materials and surfaces, such as hydrophobic and icephobic engineered cementitious composites and corrosion resistant metallic surfaces, can be produced by controlling the surface micro/nanotopography.
Keywords: Corrosion Resistance; Icephobicity; Superhydrophobicity; Surface Micro/nanotopography; Vibrations; Wetting